The binomial theorem tells us how to expand an expression of the form (a + b)^2 like this:
![(a+b)^n=nC_0a^nb^0+nC_1a^(n-1)b^1+\cdots nC_na^0b^n](https://img.qammunity.org/2023/formulas/mathematics/college/crnpl210v5wrrpel8og05zmeci5e3vvhsk.png)
And nCr is given by the following formula:
![nC_r=(n!)/(r!(n-r)!)](https://img.qammunity.org/2023/formulas/mathematics/college/5hm7rglqgm25fa15d2rko8iodp2eumgzdx.png)
Then, for this polynomial, we can apply the binomial theorem with a = x, b = -3 and n = 5 to get:
![(x-3)^5=5C_0x^5(-3)^0+5C_1x^4(-3)^1+5C_2x^3(-3)^2+5C_3x^2(-3)^3+5C_4x^1(-3)^4+5C_5x^0(-3)^5](https://img.qammunity.org/2023/formulas/mathematics/college/blqjumzeb2pqoup4u49168u83c5p8c2n5d.png)
![\begin{gathered} 5C_0=1 \\ 5C_1=5 \\ 5C_2=10 \\ 5C_3=10 \\ 5C_4=5 \\ 5C_5=1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/vu38dhstdaps8eyfjcqwazkq7pudqr5ntn.png)
Simplifying, we get:
![\begin{gathered} (x-3)^5=(1)x^5(-3)^0+(5)_{}x^4(-3)^1+(10)_{}x^3(-3)^2+(10)x^2(-3)^3+(5)x^1(-3)^4+(1)x^0(-3)^5 \\ (x-3)^5=x^5+(5)_{}x^4(-3)^{}+(10)_{}x^3(9)+(10)x^2(-27)+(5)x^1(81)^{}-243 \\ (x-3)^5=x^5-15_{}x^4^{}+90_{}x^3-270x^2+405x^{}^{}-243 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/uf7zrtjhgn1hwx3h7vivgho28r99lwcyqf.png)
Then, the expanded polynomial is:
x⁵ - 15x⁴ + 90x³ - 270x² + 405x - 243